Difficult Decisions in Thoracic Surgery An Evidence-Based Approach - Ferguson, Mark K. (Difficult Decisions in Surgery: An Evidence-Based Approach, 2014)
The third edition of Difficult Decisions in Thoracic Surgery: An Evidence-Based Approach, devotes itself to looking at questions and decisions in general thoracic surgery that are difficult or controversial. Focused topics are explored, and readers will find pithy analyses and recommendations which are carefully given in accordance with the level of supporting evidence available.   Written by recognized experts in the field, Difficult Decisions in Thoracic Surgery: An Evidence-Based Approach 3rd edition is a timely reference source for practicing surgeons, surgeons in training, and educators that describes the recommended ideal approach, rather than customary care, in selected clinical situations. .